Efeitos de uma válvula geradora de tumble no escoamento em um motor de ciclo Otto - Radicchi, Fábio de Castro (2023)
According to some recent international reports, greenhouse gas emissions still represent a global problem whose causes are associated, at least in part, with the internal combustion engines used in the transport sector. These studies also indicate a probable depletion of fossil fuel reserves in the coming decades and the difficulty in replacing combustion engines with other alternatives, which aggravates this scenario and reinforces the need to continue investigating possible improvements. Based on this, this work proposed and evaluated the use of a tumble valve in the intake system of a four-stroke engine operating with ethanol, with the main objective of improving some processes that precede combustion and occur inside the engine, such as mixture formation and air flow. The developed valve differs from other devices found in the literature due to its versatility, being composed of two interconnected and movable flaps that, when partially closed, modify the flow patterns inside the cylinder. The study carried out was essentially numerical based on computational fluid dynamics and the simulations were performed in the commercial software Converge. It was used a single-cylinder research engine, naturally aspirated, with four valves and a volumetric compression ratio of 11.5:1. A representative operating condition was chosen with an engine speed of 3000 rpm and an average intake load of 600 mbar. A method for selecting the best flap inclination through two-dimensional simulations was developed and from it the inclination of 6° was selected. Three-dimensional simulations with this configuration revealed considerable increases in the tumble coefficient and turbulent kinetic energy, which rose by about 44% near the spark plug electrode in the final moments of compression. Peak cylinder pressure increased by 12% and trapped mass by 7.2%, promoting an increase in volumetric efficiency from 77% to 85%. When using the valve intermittently, obstructing the air in only half of the possible range, the gains in pressure and cylinder filling increased to 18% and 26%. The results of simulations with direct injection of ethanol revealed smaller drops close to the instant of ignition and approximately 10% greater evaporation when using the device. With an early start of injection, the fuel spray slightly compromised the tumble values in the cylinder, but it was still possible to perceive an important load stratification that did not occur in the original engine. Finally, with a late fuel injection, less interference was noticed on the tumble values and an even more pronounced gain of about 33% in fuel evaporation. In this way, this work exposed in detail the main effects of the tumble generator valve and proved that the associated gains go beyond the intensification of this movement, being very promising for the improvement of engine performance.